Technological integration of marketing in the supply chain of a transport company - Vaičiūtė, Kristina; Išoraitė, Margarita (Business: Theory and Practice, 2023)
The speed of movement of goods, information and services determines the success and the efficiency of a transport company that wants to meet the needs of the customer. Consumers want better quality services, greater variety of products, more innovation and better service, but at a lower price, and in a shorter time. To fully satisfy the expectations of the consumers, a very large part of the role in business enterprises is played by the supply chain, the management of its processes, and ensuring the efficiency of them. The study involved 8 experts. One of the most important characteristics of experts is competence, therefore experts were required to have competence and experience in the field under investigation. Everyone must have a higher education and work experience of at least 5 years. All experts have 5–10 years of management experience in the supply chain of Lithuanian transport companies and have a higher education. The experts were asked to evaluate the main factors that determine the effectiveness of technological integration of marketing in a supply chain of a transport company. According to the experts’ assessments and calculations, the list of the importance of the main criteria of the impact of marketing technological integrations in the supply chain of a transport company should be arranged in the following order: customer relationship management in the supply chain, fast transmission of the information in the supply chain, electronic auctions in the supply chain, product innovations in the supply chain, and electronic catalogs in the supply chain.